The prevalence and correlates of behavioral risk factors for cardiovascular health among Southern Brazil adolescents: a cross-sectional study - Barbosa Filho Valter; de Campos Wagner; Bozza Rodrigo; Lopes Adair da (BMC, 2012)
Abstract Background The adoption of health-related behaviors is an important part of adolescence. This study examined the prevalence and correlates of the isolated and simultaneous presence of behavioral risk factors for cardiovascular health (BRFCH) among adolescents in Curitiba, Southern Brazil. Methods A cross-sectional study was performed with 1,628 adolescents (aged 11-17.9 years, 52.5% males) that were randomly selected from 44 public schools. Self-report instruments were used to assess the variables. Six BRFCH were analyzed: insufficiently active, excessive TV watching, current alcohol and tobacco use, daily soft drinks consumption and inadequate fruit and vegetable consumption. Sociodemographic and behavioral variables were studied as possible correlates of the presence of BRFCH. Results The BRFCH with the highest prevalence were insufficiently active (50.5%, 95% confidence interval [95% CI]: 48.0-52.9) and daily soft drinks consumption (47.6%, 95% CI: 45.1-50.0). Approximately 30% of the adolescents presented three or more BRFCH simultaneously. Girls, adolescents who did not participate in organized physical activity, and who used computer/video games daily were the main high-risk subgroups for insufficiently active. Boys and those who used computer/video games daily were the high-risk subgroups for daily soft drinks consumption. For excessive TV watching, we identified to be at risk those who were from a high economic class, unemployed, and who used computer/video games daily. For current alcohol use, we identified older adolescents, who were from a high economic class and who worked to be at risk. Older adolescents, who worked and who spent little active time during a physical education class were the high-risk subgroups for current tobacco use. For inadequate fruit and vegetable consumption, we identified those who did not participate in organized physical activity to be at risk. Older adolescents, who were from a high economic class, who did not participate in organized physical activity and who used computer/video games daily were the high-risk subgroups for simultaneous BRFCH. Conclusions We found a high prevalence of BRFCH among adolescents, both isolated and simultaneously. The correlates of the presence of BRFCH can contribute to healthy policies among Brazilian adolescents, mainly focusing on high-risk subgroups for a health risk behavior.